Proses Pembuatan Mesin Pencacah Rumput Gajah Dengan Kapasitas 1000 kg / Jam - Iwan Setiawan (Jurusan t.Mesin Fakultas Teknik UMY, 2011)
Proses Pembuatan Mesin Pencacah Rumput Gajah Dengan Kapasitas 1000 kg / Jam